Productivity of Local Goats Supplemented with Acacia villosa and Coripha gebanga - A M Fuah; W A Pattie (Faculty of Animal Science, Bogor Agricultural University, 2013)
Most feed for goats in the villages of West Timor, Indonesia, came from communal grazing areas, consist of native grass during wet season, crop residues and tree leaves (Sesbania and Acacia species) in dry season. This study was aiming at examining the growth of goat supplemented with local feed. Twenty four goats were used, the average initial live weight was 12.5 kg. Four feeding treatments were applied: T1-200 g cut grass; T2-200 g Acacia villosa; T3-200 g Coripha gebanga; T4-100 g A. villosa + 100 g C. gebanga. Live weights and feed consumption were analyzed using repeated measures, analysis of variance. The average live weight showed a small increase, as well as daily weight gain of goats of which different significantly (PA. villosa, C. gebanga, and A. villosa plus C. gebanga, respectively. Goats given C. gebanga and mixed Acacia and C. gebanga gave higher average weight gain, but also consumed more feed than those given cut grass or A.villosa (P < 0.01). Supplementing feed to maintain growth of goats during dry seasons was better on A. villosa than on palm pith and its combination.